CONTROLE DE POLUIÇÃO DAS ÁGUAS SUBTERRÂNEAS DA REGIÃO DO VALE DO RIO PARAÍBA - E SILVA, CARLOS CELSO DO AMARAL; AMIR, YIGAL; PENA, YARA MONTEIRO DE ARRUDA DAMASCO (Águas Subterrâneas, 1980)
RESUMO NÃO DISPONÍVEL